IDENTIFIKASI KEPRIBADIAN ANAK PELAKU TINDAK PIDANA SEBAGAI DASAR PENYELESAIAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK: (Studi Pada Unit PPA Satreskrim Polres Pariaman) - Dinata, Richie Viata (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
At the Pariaman District Police Criminal Investigation Unit there are many criminal cases involving minors as perpetrators of criminal investigations. Therefore an investigation is needed to identify the Personality of Children of Criminal Actors by the Pariaman District Police Chief of Criminal Investigation. Identification of criminal investigations by children is carried out with several techniques, including some by interviewing children who are indicated as perpetrators of crime and also by reporting from the public. Crimes involving children as perpetrators of crime are not only caused by genetic factors but also due to lack of supervision from parents and the influence of the social environment and place of residence, therefore the role of parents and us together is expected to be more active in supervising children